2020
DOI: 10.33790/jphip1100170
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Systems Theory: Exploring the Development of the Theoretical Framework as Conceived by Bronfenbrenner

Abstract: The Ecological Systems theory represents a convergence of biological, psychological, and social sciences. Through the study of the ecology of human development, social scientists seek to explain and understand the ways in which an individual interacts with the interrelated systems within that individual’s environment (Bronfenbrenner, 1983a). Bronfenbrenner (1994) sought to develop a theory of human development that would consider the influences of all of the systems that play a role in impacting the lived expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
0
33
0
3
Order By: Relevance
“…This is alternatively called cultural capital and may enhance or inhibit learning especially if the learning environment is biased or not inclusive of the differences among learners (Cobern, 1996). The learner is influenced, according to Bronfenbrenner's ecological systems theory, by various spheres with which they interact (Crawford, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is alternatively called cultural capital and may enhance or inhibit learning especially if the learning environment is biased or not inclusive of the differences among learners (Cobern, 1996). The learner is influenced, according to Bronfenbrenner's ecological systems theory, by various spheres with which they interact (Crawford, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a male who has not acknowledged impregnating a female through compensating the female's family will be denied access to his child. Crawford (2020) confirmed that although many fathers are reluctant to pay damages and follow cultural practices of the maternal family, they end up agreeing for the sake of their children. Ecosystems theory hold the view that old community members hold an important position that everyone is expected to respect hence these fathers have no choice but to find means to provide for their children.…”
Section: Financial Incapacity As a Contributing Factor To Crimementioning
confidence: 95%
“…It was initially looking at the science of living organisms (Ecology) but later moved to ecosystems theory that aims to understand the relationship between individuals and their environment (Weyers, 2011). According to Crawford (2020), Bronfenbrenner (1976 understood that many theories are based on understanding individuals in isolation and came up with one that will uncover how the immediate systems of an individual affect their development and how these individuals' affects the systems. In other words, the ecosystems theory is embedded in comprehending how individuals relate to one another and how the environment comes about affecting their lives.…”
Section: Theoretical Framework Applicationsmentioning
confidence: 99%
See 2 more Smart Citations